Eficácia das técnicas de coleta para a adequabilidade da amostra colpocitopatológica: ensaio clínico randomizado controlado - Freitas, Vívien Cunha Alves (2019)
The objective is to test the effectiveness of collection techniques for adequacy of the colpocytopathological sample. This is an experimental Randomized Controlled Trial study without comparing two smear collection techniques from the Pap smear, listed in two groups: Control Group (CG) (how ectocervix cells were fixed in the sample and after collecting as endocervic cells - Brazilian recommendations from 2006) and the Intervention Group (GI) (as ectocervic cells that were discarded after collection of endocervical cells - used for 2013). Study developed at the Lígia Barros Costa Natural Birth Center (CPN), in Fortaleza-CE, from September 2018 to July 2019. At the end, we registered a sample of 184 women in the CG and 181 in the GI, totaling 365 participants, allocated by block randomization strategy in the mentioned groups. Blinding was guaranteed to the patient, the cytopathologist who assessed the adequacy of the sample and the statistics. Data were collected through a questionnaire, including sociodemographic, clinical, sexual and reproductive variables and related to the findings in the cytopathological report. Data were analyzed using the Windows Statistical Package for Social Sciences (SPSS) software version 22.0, using Kruskal-Wallis, Chi-square and Fisher tests. One research was approved by the Research Ethics Committee of the Federal University of Ceará (CEP/PROPESQ/UFC) and registered in the Brazilian Registry of Clinical Trials (ReBEC) platform. Regarding the identification of differences between the groups, recorded if they were homogeneous among the related variables (p> 5%), allowing statistical inferences. Regarding the adequacy of the sample and the other cytopathological findings, there were no significant differences in the technical relation of collection (p = 0.362) and in the sociodemographic, clinical, sexual and reproductive aspects did not affect the adequacy of the sample, obtaining the value of p > 5% in all listed variables. Therefore, the technical standards applied in cytopathological collectives, published in 2006 and 2013, are used to use an experimental sample; should have an update of the manual dealing with these precautions, avoid guidelines that do not influence the clinical practice. It is a study of high scientific evidence, published in the area.